Elastic-plastic analysis of curved grid structures - Tsai, Hsien-jen; Usami, Tsutomu; Karasudhi, Pisidhi; Pichai Nimityongskul; Government of Republic of China (Bangkok : Asian Institute of Technology, 1978)
A matrix displacement method has been presented for analyzing the elastic-Plastic behavior of curved grid structures. The yield function for combined bending and torsion is incorporated in the analysis together with the associate flow rule. The method is feasible for tracing the complete load-deflection relationship of any type of curved grid structures up to collapse state.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Grillages (Structural engineering)